2018
DOI: 10.1073/pnas.1718670115
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate modulates stem cell dynamics in Arabidopsis shoot meristems through cytokinins

Abstract: The shoot apical meristem (SAM) is responsible for the generation of all the aerial parts of plants. Given its critical role, dynamical changes in SAM activity should play a central role in the adaptation of plant architecture to the environment. Using quantitative microscopy, grafting experiments, and genetic perturbations, we connect the plant environment to the SAM by describing the molecular mechanism by which cytokinins signal the level of nutrient availability to the SAM. We show that a systemic signal o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(147 citation statements)
references
References 32 publications
9
127
0
Order By: Relevance
“…However, evidence that nitrate signaling can directly interact with the flowering network at the SAM has not yet been reported. A recent publication describes a root‐borne cytokinin signal that transduces nitrate availability to the SAM within a matter of days and controls the stem cell population and hence meristem size and growth (Landrein et al ., ). It remains an open question whether this systemic signal also contributes to the regulation of flowering as previously suggested (D'Aloia et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, evidence that nitrate signaling can directly interact with the flowering network at the SAM has not yet been reported. A recent publication describes a root‐borne cytokinin signal that transduces nitrate availability to the SAM within a matter of days and controls the stem cell population and hence meristem size and growth (Landrein et al ., ). It remains an open question whether this systemic signal also contributes to the regulation of flowering as previously suggested (D'Aloia et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Coordinated energy allocation between root and shoot growth is essential for optimizing whole‐plant performance. New studies using grafting have identified signaling molecules that coordinate root–shoot responses to drought stress (Takahashi et al ., ), light (Chen et al ., ), and nitrogen (N) availability (Tabata et al ., ; Chen et al ., ; Ohkubo et al ., ; Landrein et al ., ).…”
Section: Systemic Signals For Drought Stress Starvation and Sunlightmentioning
confidence: 97%
“…Low‐N conditions induce the expression of C‐ TERMINALLY ENCODED PEPTIDE ( CEP ) peptides in roots (a), which were shown to travel into the shoot where they bind CEP receptors (c; highlighted in blue) and trigger the expression of CEP ‐ DOWNSTREAM ( CEPD ) response peptides (highlighted in pink) that move back down into the root to induce NRT 2.1 expression in a nitrate‐dependent manner (d) (Tabata et al ., ; Ohkubo et al ., ). High‐nitrate conditions in roots activate the production of trans ‐Zeatin cytokinin precursors (highlighted in purple), which were shown, through genetic grafting experiments (e), to move through the xylem into shoots where they participate in the regulation of shoot apical meristem (SAM) size (Osugi et al ., ; Landrein et al ., ). Note that (b–e) illustrate key reciprocal grafting experiments that were used to demonstrate the movement of long‐distance N signals, but are not meant to illustrate all grafting experiments used in the discoveries described.…”
Section: Systemic Signals For Drought Stress Starvation and Sunlightmentioning
confidence: 97%
See 2 more Smart Citations